2021
DOI: 10.1016/j.jbc.2021.100491
|View full text |Cite
|
Sign up to set email alerts
|

SSSPTA is essential for serine palmitoyltransferase function during development and hematopoiesis

Abstract: Serine palmitoyltransferase complex (SPT) mediates the first and rate-limiting step in the de novo sphingolipid biosynthetic pathway. The larger subunits SPTLC1 and SPTLC2/SPTLC3 together form the catalytic core while a smaller third subunit either SSSPTA or SSSPTB has been shown to increase the catalytic efficiency and provide substrate specificity for the fatty acyl-CoA substrates. The in vivo biological significance of these smaller subunits in mammals is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…On the other hand, the generation of CMPs was significantly depleted, indicating an important role of SPTLC1 in granulopoiesis. Building upon these findings, this group continued their investigation of SPT in hematopoiesis, and they also revealed a role for ssSPTa in myelopoiesis similar to that of SPTLC1 [133]. Specifically, the loss of ssSPTa, but not of ssSPTb, from adult HSCs using Mx-1-Cre mice led to specific impairment of myelopoiesis with increased Lin − Sca1 + c-Kit + stem cells, as well as increased progenitors.…”
Section: Sphingolipids In Myeloid Differentiationmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, the generation of CMPs was significantly depleted, indicating an important role of SPTLC1 in granulopoiesis. Building upon these findings, this group continued their investigation of SPT in hematopoiesis, and they also revealed a role for ssSPTa in myelopoiesis similar to that of SPTLC1 [133]. Specifically, the loss of ssSPTa, but not of ssSPTb, from adult HSCs using Mx-1-Cre mice led to specific impairment of myelopoiesis with increased Lin − Sca1 + c-Kit + stem cells, as well as increased progenitors.…”
Section: Sphingolipids In Myeloid Differentiationmentioning
confidence: 88%
“…Specifically, the loss of ssSPTa, but not of ssSPTb, from adult HSCs using Mx-1-Cre mice led to specific impairment of myelopoiesis with increased Lin − Sca1 + c-Kit + stem cells, as well as increased progenitors. [133]. Molecularly, the defect in myelopoiesis was accompanied by evidence of ER stress.…”
Section: Sphingolipids In Myeloid Differentiationmentioning
confidence: 99%
“…The importance of BA-regulated ER stress signaling in HSCs is further supported by seminal works from the Miharada lab which demonstrated that fetal HSCs exhibit low levels of adaptive responses to ER stress that significantly depend on BA chaperone activity for expansion and differentiation [203,204]. As such, the involvement of ER stress signaling in HSC homeostasis is gaining momentum in research, as seen in several new reports on this topic [205][206][207][208][209]. Importantly, the mechanism that allows ENT3 to regulate erythroid pool size introduces a new concept into the understanding of stress-adaptive ER stress signaling in HSCs [207].…”
Section: A Role For Nucleoside Transporters In Mammalian Hematopoiesismentioning
confidence: 92%
“…As such, the involvement of ER stress signaling in HSC homeostasis is gaining momentum in research, as seen in several new reports on this topic [205][206][207][208][209]. Importantly, the mechanism that allows ENT3 to regulate erythroid pool size introduces a new concept into the understanding of stress-adaptive ER stress signaling in HSCs [207]. More intriguingly, the ENT3 loss-induced defects in ER stress signaling are not only evident in HSCs but were also observed along the erythroid line of differentiation including hematopoietic progenitors and precursors, which are major targets of anticancer nucleoside analogs.…”
Section: A Role For Nucleoside Transporters In Mammalian Hematopoiesismentioning
confidence: 99%
“…Serine palmitoyltransferase (SPT) is a key enzyme in sphingolipid biosynthesis and catalyzes the pyridoxal 5 0 -phosphate (PLP)-dependent decarboxylative condensation of l-serine (l-Ser) with palmitoyl-CoA (PalCoA) to generate 3-ketodihydrosphingosine (Hanada, 2003). Eukaryotic SPT is a membrane-bound enzyme composed of two core subunits named SPTLC1 and SPTLC2/SPTLC3 (Buede et al, 1991;Nagiec et al, 1994;Hornemann et al, 2006) that are associated with the regulatory components ssSPTa/ssSPTb and ORMDL3 (Parthibane et al, 2021;Chauhan et al, 2016;Han et al, 2009;Gable et al, 2000;Breslow et al, 2010). SPT is essential for cell viability in eukaryotes, and alterations in SPT activity caused by mutations of either the SPTLC1 or the SPTLC2 gene are linked to neurodegenerative diseases such as hereditary sensory and autonomic neuropathy type I (HSAN1) in humans (Bejaoui et al, 2001;Dawkins et al, 2001;Hornemann et al, 2009;Rotthier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%